2018
DOI: 10.1016/j.cell.2018.05.051
|View full text |Cite
|
Sign up to set email alerts
|

Common Disease Is More Complex Than Implied by the Core Gene Omnigenic Model

Abstract: The evidence that most adult-onset common diseases have a polygenic genetic architecture fully consistent with robust biological systems supported by multiple back-up mechanisms is now overwhelming. In this context, we consider the recent "omnigenic" or "core genes" model. A key assumption of the model is that there is a relatively small number of core genes relevant to any disease. While intuitively appealing, this model may underestimate the biological complexity of common disease, and therefore, the goal to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
215
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(238 citation statements)
references
References 80 publications
(72 reference statements)
16
215
1
1
Order By: Relevance
“…Nonetheless, the prevalence and distribution of loci we identified are similar to recent mapping experiments in S. cerevisiae that also had high power to detect loci with opposing effects on quantitative traits (Jakobson and Jarosz 2019). They are also consistent with models of complex traits, such as the "omnigenic model" (Boyle et al 2017;Wray et al 2018;Liu et al 2019); our work specifically supports the idea that many casual variants have trans-regulatory effects on expression.…”
Section: Resultssupporting
confidence: 86%
“…Nonetheless, the prevalence and distribution of loci we identified are similar to recent mapping experiments in S. cerevisiae that also had high power to detect loci with opposing effects on quantitative traits (Jakobson and Jarosz 2019). They are also consistent with models of complex traits, such as the "omnigenic model" (Boyle et al 2017;Wray et al 2018;Liu et al 2019); our work specifically supports the idea that many casual variants have trans-regulatory effects on expression.…”
Section: Resultssupporting
confidence: 86%
“…(26) These results suggest that 1) the effect-size of deletions on NVIQ can be estimated using constraint scores, such as the "probability of being Loss-of-function Intolerant" (pLI, definition in textbox, Figure 1) (27), and 2) the effect of haploinsufficiency on NVIQ applies to a large proportion of the genome, consistent with a highly polygenic model. (28,29) Using pLI as an explanatory variable, we estimated that one third of the coding genes affect NVIQ by >1 point, when deleted.…”
Section: Introductionmentioning
confidence: 99%
“…These analyses confirmed the validity of our previous suggestion about herpesviruses as a component cause of MS and showed that this is not common to the other diseases considered in this study.A related issue is the clarification of the biological consequences of the observed associations. Elegant studies are resolving the functional implications of individual disease-associated variants (Gregory et al, 2012;Steri et al, 2017).Given the complex nature of multifactorial diseases (Wray et al, 2018), and particularly for translation into clinical benefit, a more general understanding of how gene-environment interactions generate gene expression alterations is also necessary (Gallagher and Chen-Plotkin, 2018). We therefore analyzed transcriptomes from the peripheral blood of persons with MS to verify whether genes that are nominally associated with MS, and are part of our interactomes, were more frequently present among dysregulated genes (see workflow in Figure1).…”
mentioning
confidence: 99%
“…Given the complex nature of multifactorial diseases (Wray et al, 2018), and particularly for translation into clinical benefit, a more general understanding of how gene-environment interactions generate gene expression alterations is also necessary (Gallagher and Chen-Plotkin, 2018). We therefore analyzed transcriptomes from the peripheral blood of persons with MS to verify whether genes that are nominally associated with MS, and are part of our interactomes, were more frequently present among dysregulated genes (see workflow in Figure1).…”
mentioning
confidence: 99%